Autonomy and self-determination : between legal assertions and utopian aspirations - Hilpold, Peter, 1965- (Edward Elgar Publishing, 2018)
Europe has reached a crisis point, with the call for self-determination and more autonomy stronger than it ever has been. In this book, renowned international lawyers give a detailed account of the present state of international law regarding self-determination and autonomy. Autonomy and Self-determination offers readers both an overview of the status quo of legal discussions on the topic and an identification of the most important elements of discussion that could direct future legal developments in this field. This is done through the examination of key issues in abstract and in relation to specific cases such as Catalonia, Italy and Scotland. The book extends past a simple assessment of issues of autonomy and self-determination according to a traditional legal viewpoint, and rather argues that utopian international law ideas are the breeding ground for norms and legal institutions of the future. This insightful book will be an invaluable read for international lawyers and political science scholars. It provides a clear, yet detailed, analysis of the issues Europe is facing regarding autonomy and self-determination in the face of historical context, also making it a useful tool for European history scholars.